"One Size Does Not Fit All:" A Proposed Ecological Model for Human Trafficking Intervention. Issue 2 (4th March 2018) - Barner, John R.; Okech, David; Camp, Meghan A.
ABSTRACT: The problem of human trafficking continues to be one of the vilest human rights abuse and manifestation of social injustice around the world. A lot of antitrafficking efforts have been put in place. However, there is still a lot of emphasis on the criminal aspect of the problem. This has meant that human and practical aspects of the problem have not received sufficient attention, including assessing the problem, victims, and perpetrators in their environments. The ecological perspective helps practitioners, researchers, and policy makers to better understand the problem. This article uses the main concepts in this theory to frame the problem. Discussions are directed toward understanding the different aspects of the problem from an ecological perspective.